Exploring phytochemicals and pharmacological properties of Populus × tomentiglandulosa - Lee, Hak-Dong; Kim, Ji Hyun; Choi, Jong Hee; Kim, Ki Hyun; Ku, Jajung; Choi, Kyung; Kim, Hyun Young; Lee, Sanghyun; Cho, Ik-Hyun (Frontiers in Pharmacology, 2024)
Populus tomentiglandulosa (PT), a tree endemic to Korea, shows promising potential as a natural therapeutic agent owing to its potent antioxidant and anti-inflammatory properties.However, the isolation and analysis of phytochemical components in PT and related species remains underexplored. Therefore, this study aims to investigate the biochemical profile of PT and evaluate its extracts and fractions for antioxidant and anti-inflammatory activities. Nine compounds were isolated, including two novel flavonoids (luteolin 7-O-β-D-glucuronide butyl ester and chrysoeriol 7-O-β-D-glucuronide butyl ester) from the Salicaceae family for the first time. The ethyl acetate fraction exhibited significant radical scavenging activity across all in vitro antioxidant assays (DPPH, ABTS + , • OH, and O2 -). PT extracts and the ethyl acetate fraction showed minimal cytotoxicity in Raw 264.7 macrophages at concentrations below 500 and 100 µg/mL, respectively. Furthermore, PT extracts and fractions significantly suppressed the protein expression of proinflammatory mediators (iNOS and IL-6) in LPS-stimulated Raw 264.7 macrophages, highlighting their potent anti-inflammatory effects. These findings suggest that PT holds promise as a valuable natural therapeutic intervention for various oxidative stress and inflammation-related disorders, underscoring the need for further exploration of its clinical applications.